ANALISIS HUBUNGAN PANJANG-BERAT DAN FAKTOR KONDISI IKAN LELE MOMA (Clarias meladerma) DI AEK SILOM LOM LABUHANBATU SELATAN - Sindi Pratiwi Ningsih; Rusdi Machrizal (Jurnal Biosilampari : Jurnal Biologi, 2022)
Clarias meladerma Bleeker, 1846 is one of the native species in Indonesia. Aek Silom Lom is one of the habitats of catfish moma (C. meladerma) located in Labuhanbatu district. The study was conducted to analyze the long-weight relationship and the condition factors of catfish moma (C. meladerma) that live in Aek Silom Lom. Sample collected from October- December 2021. Sample was taken by angler. This weight length relationship is calculated using the linear allometric model (LAM), while the condition factor is calculated using the fulton formula (K) and relative weight (Wr). The growth pattern of catfish moma (C. meladerma) in Aek Silom lom is allometric negative with a value of b 0.99 (b<3), this means that the growth of the fish's body length is faster than the body weight. The fulton coefficient (K) is between 14,889 -17.1292 and the relative weight coefficient (wr) is in the range of 97.32805-100.0745, indicating that the condition of the catfish population (C. meladerma) is in balance and the water conditions of Aek Silom Lom can support the life of the catfish moma (C. meladerma)